PRESIDEN PEREMPUAN: STUDI ATAS PANDANGAN KIYAI HUSEIN MUHAAMMAD - Gazali, Gazali; Syafrizal, Syafrizal (Living Islam: Journal of Islamic Discourses, 2020)
This article addresses the issue of a female president according to K.H. Husein Muhammad. This figure is used as a reference material, first, because of his high attention to gender issues. Second, women's leadership in Indonesia is a discourse and vehicle that develops dialectically and is very interesting to be used as a reference material, especially since Indonesia is the largest Muslim country in the world where gender issues are still in the "debateble" category. This article is a literature review using the inductive methodology, by compiling the works of the figures studied to draw conclusions related to the issues discussed. From this article conclusions are drawn; 1) Analysis in terms of women's leadership Kiyai Husein allowed it because the verse that spoke about male leadership was born from patriarchal culture. 2) While the traditions that talk about women's leadership are traditions that have asbabun nuzul about the leadership of women who are disputed / arbitrary and the traditions must be understood in terms of al ibrah bi specialization sabab la bi'umumil lafzhi and that hadith is not in the context of legal legitimacy but just a notification.